The role of translation in the interconnection of literature (Eurasian Journal of Philology Science and Education, 2023)
The article considers the development process of Kazakh literature, and the characteristics of ideological and aesthetic novelty in the context of world culture. It determines the manifestations of common patterns,  poetic integrity in the cultural and literary development of humanity in Kazakh literature, and the typological connections between the literatures. The article also shows the role of methods of comparative literature in revealing mentioned features. Comparing the literature of nations at the same socio-historical stage of development, the concepts of several scientific schools are evaluated, which show ways to reveal the patterns of common literary phenomena in the academic process. Based on the interdependence and similarities of several kinds of literature, the study provides a comprehensive analysis of the ideas of «universal literature» and «international trends»  derived from the analysis of standard  features found in the literature of several peoples. At the same time, with the collapse of the world colonial system and over time, the common patterns that will be preserved in the literature of nations that have entered the path of independent political, cultural and socio-historical development of countries which become genetically united will be revealed. The coexistence of the literature of the «old» nations and the literature of the «new» nations, which took place at the highest stages of artistic development, is an example of the fact that literary development differed in each nation. One of the significant issues in the article is the recent experience of European countries in the literature of certain nations (including Kazakh literature) in the epochs of classicism, romanticism, realism, naturalism, modernism etc. In the XIX-XX centuries, the influence of the Western, including European, impact on the literary and cultural development of the Kazakhs was much greater than the influence of the East.